ION MICROPROBE U-PB DATING OF ZIRCON FROM A MONVISO METAPLAGIOGRANITE: IMPLICATIONS FOR THE EVOLUTION OF THE PIEDMONT-LIGURIA TETHYS IN THE WESTERN ALPS - Lombardo, Bruno; Rubatto, Daniela; Castelli, Daniele (Ofioliti, 2002)
The Monviso metamorphic ophiolite, one of the best preserved relics of oceanic crust in the Western Alps, was formed during the opening of the Mesozoic Western Alpine Tethys and underwent metamorphism to eclogitic conditions during Alpine subduction. The Monviso ophiolite encompasses the whole lithological spectrum of the Piedmont-Liguria ophiolite rocks, with a basal unit of serpentinized peridotite in tectonic contact with the overlying metagabbros, eclogites and pillowed metabasalts. Slivers of serpentinized peridotite hosting banded eclogites and metagabbros divide these units from the overlying Forciolline Unit. The latter (formerly called Costa Ticino Series) is an overturned sequence of gabbros with pods of cumulate troctolite and lenses of serpentinized peridotite, overlain by massive and pillow metabasalts. A unit of massive metabasalts tops the tectonic stack. A body of jadeite-quartz bearing metaplagiogranite has been recently found in the Basal Serpentinite Unit near Vernè, northwest of Sampeyre, Val Varaita. Zircon crystals recovered from the Vernè metaplagiogranite have large domains with typical magmatic zoning with broad oscillatory bands. They have Th/U ratios in the range 0.3-0.7, as commonly observed in magmatic zircon. In situ ion microprobe (SHRIMP) U-Pb dating of the magmatic domains yielded a mean age of 152±2 Ma, which is interpreted as the crystallization age of the Monviso plagiogranite. Unzoned domains that crosscut magmatic zircon yielded younger, apparent ages which are most likely due to Pb loss during Alpine metamorphism. In conjunction with previous works on ophiolites from the Western Alps, Northern Apennines, and Alpine Corsica, the new data from Monviso suggest that the plutonic activity in the Piedmont-Liguria domain of the western Tethys may have lasted only 15 to 20 Ma, between ca. 170 and ca. 150 Ma. As shown by Radiolarian biostratigraphy, this is approximately the same time span encompassed by the extrusion of tholeiite basalts which cap both the gabbro plutons and their peridotite country rocks. The new data indicate that the plutonic activity recorded at Monviso was coeval with basalt extrusion and deep-sea sediment deposition in some Liguriantype ophiolite bodies of the Cottian Alps. This suggests that the oceanic crust preserved in the Monviso ophiolite may have formed later, and in a more central position of the basin, than the oceanic crust preserved in such Ligurian-type ophiolite bodies.